Enamel color changes following orthodontic treatment - Akshaya Pandian; Sukanya Ranganathan; Sridevi Padmanabhan (Wolters Kluwer Medknow Publications, 2017)
Objective: To evaluate and compare the effect of various orthodontic bonding systems and clean up procedures on quantitative enamel colour change. Materials and Methods: A literature search was done to identify the studies that assessed the quantitative enamel colour change associated with the various bonding systems and cleanup procedures. Electronic database (Pub Med, Cochrane and Google Scholar) were searched. First stage screening was performed and the abstracts were selected according to the initial selection criteria. Full text articles were retrieved and analyzed during second stage screening. The bibliographies were reviewed to identify additional relevant studies. Results: Sixteen full text articles were retrieved. Six were rejected because the methodology was different. There was significant enamel colour change following orthodontic bonding, debonding and clean up procedures. Conclusion: Self-etching primers produce less enamel colour change compared to conventional etching. Resin Modified GIC produces least colour change compared to other light cure and chemical cure systems. Polishing following the clean-up procedure reduces the colour change of the enamel.